Case report: First treatment of acute ischaemic stroke in a patient on active rivaroxaban therapy using andexanet alfa and rtPA combined with early complete recovery - Karaszewski, Bartosz; Szczyrba, Sebastian; Jabłoński, Bartosz; Gąsecki, Dariusz; Kraszewski, Piotr; Wyszomirski, Adam; Kowalski, Robert; Kaliszan, Wioletta; Dąbrowska, Małgorzata (Frontiers in Neurology, 2023)
Patients with non-large vessel occlusion acute ischemic stroke (NL-AIS) on oral anticoagulants (OAC) constitute the biggest portion among those who cannot receive any potential-reperfusion treatment even if they appear early in the hospital. We present the first case of therapy for NL-AIS in a patient with active anti-Xa anticoagulation, combining andexanet alfa and rtPA, who was recruited for STRoke On AntiCoagulants for Thrombolysis (acronym: STROACT), an ongoing therapeutic trial for non-LVO ischemic stroke on a DOAC. This is also the first report of the use of andexanet alfa-rtPA for AIS in a patient on rivaroxaban, which is the most frequently used non-vitamin K antagonist oral anticoagulant. The patient received the intravenous bolus of 800 mg of andexanet (contralateral arm), followed by a bolus of rtPA (10% of the calculated dose; ipsilateral arm), then a continuous infusion of andexanet at 8 mg/min for 120 min (contralateral arm), and rtPA (90% of the calculated dose; ipsilateral arm)—both stopped after completion of 38.9 and 74% of infusion dose, respectively, due to the severe adverse event related to the administration of rtPA. In this schema, both infusions are ongoing concurrently for approximately 60 min, and then andexanet is administered alone until the completion of the dose (altogether lasting approximately 3 h). The therapy was spectacularly effective, with early and complete improvement in NIHSS from 8 to 0 points in 70 min from the initiation of the therapy; mRS = 0. Obviously, a single case cannot drive any standard therapeutic decisions, but the experience we share in this article may help manage selected special clinical problems, especially when a patient's expected outcome is poor and there is no other way to help than experimentally. Additionally, it seems a valuable addition to recent meta-data on thrombolysis in anticoagulated patients. Trial registration https://www.clinicaltrialsregister.eu. Identifier: 2020-004898-41. Date of registration: March 31, 2021.